Treatment of IgA Nephropathy of Adults Presented by Nephrotic Syndrome - Senija Rašić; Snježana Unčanin; Kenana Aganović; Ismar Rašić; Jasminka Džemidžić; Alma Muslimović (Biomolecules & Biomedicine, 2008)
The aim of this retrospective study was to evaluate the results of the immunosuppressive regiment in managing of IgA nephropathy associated with primary nephrotic syndrome at the Nephrology Clinic, University of Sarajevo Clinics Centre in period of 1997-2007.